Burden of Caregiver for People with Schizophrenia in Sidoarjo Regency - Fahmi Yudin; Citra Fitri Agustina (Junior Medical Journal, 2023)
Schizophrenia is a severe mental disorder that leads to a decrease in the sufferer's daily functioning. People with schizophrenia need medical treatment and good treatment through their families to achieve their recovery. Families also have an obligation to carry out their responsibilities in caring for their family members, including those with schizophrenia. The purpose of this study is to describe the demographic description of caregivers for people with schizophrenia in Sidoarjo district and to identify more deeply the level of burden experienced by families of people with schizophrenia in Sidoarjo district. The method used in this study is descriptive quantitative method. The research instruments used were demographic data and informed consent, and a questionnaire (Zarit Burden Interview). The results showed that from 170 respondents it was shown that the majority of the burden of caring for people with schizophrenia in Sidoarjo Regency was little or no as many as 75 people (44.1%) and mild to moderate as many as 72 people (42.4%).